The molecular mechanism underlying in vitro wound healing property of Stryphnodendron astringent (Mart.) - Luiza Kaspary Pellenz, Neida; Henrique Mastella, Moisés [UNESP]; Farina Azzolin, Verônica; Ferreira Teixeira, Cibele; Köhler Carpilovsky, Paula; Muller Brunelli, Lucas; Köhler Carpilovsky, Cristiane; Hilda Costabeber, Ijoni; Beatrice Mânica da Cruz, Ivana; Maria Medeiros Frescura Duarte, Marta; Barbisan, Fernanda (EDIPUCRS, 2025)
Aim: to analyze the mechanism of the hydroalcoholic extract of barbatimão in the induction of healing in dermal fibroblast cells (HFF-1), in an in vitro model. Methods: two concentrations of barbatimão used in commercial ointments were studied here (B1 = 0.49 mg/mL; B2 = 0.99 mg/mL), and their effects were evaluated with the following markers at 24 and 72 hours after induction of the in vitro wound: (1) oxidative metabolism [DNA oxidation, lipoperoxidation, protein carbonylation, antioxidant enzymes (superoxide dismutase, SOD; catalase, CAT; glutathione peroxidase, GPX)]; (2) pro-inflammatory cytokines (TNF-, interleukin 6); (3) apoptotic markers [caspase 3 (CASP3), CASP8, and growth factors: keratinocyte growth factor (KGF) and fibroblast growth factor-1 (FGF-1)]. Results: treatment with both concentrations showed a decrease in pro-oxidant, pro-inflammatory, and pro-apoptotic markers, while increasing antioxidant levels and growth factors. Conclusions: barbatimão acts through a pleiotropic cascade mechanism involving antioxidant, anti-inflammatory, anti-apoptotic, and fibroblast migration/ proliferation modulation. Our data could explain the effect and importance of barbatimão extract in wound healing mechanisms.
Mecanismo molecular subjacente à propriedade de cicatrização de feridas in vitro do Stryphnodendron adstringens (Mart.)
Keywords: anti-inflammatory; antioxidant; polyphenols; wound healing